Shifts of agency in translation: a case study of the Chinese translation of Wild Swans - Li, Long (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2020)
This paper calls for a reconsideration of transitivity as a useful analytical tool in descriptive translation studies, especially for the investigation of the translation of agency. Transitivity is the ensemble of lexico-grammatical resources that “represent reality in language” (Eggins 2001/2005: 206). Such choices in translation have been usefully explored by a number of translation scholars with a strong orientation towards Systemic Functional Linguistics (SFL), although there has not been much recent scholarly interest within the wider community of translation studies (TS), perhaps due to the perceived complexity of SFL’s analytical framework. This paper returns to transitivity analysis for its continued relevance to TS, especially for those interested in uncovering the way agency, ideology, characterization and narrative are manifested in text. This paper incorporates new linguistic methodologies of analysing transitivity in combination with additional linguistic systems of voice, theme, and modality because this combination allows for a more holistic view of transitivity. Focusing on the translation of Mao’s agency at the beginning of the Cultural Revolution in Chang’s politically volatile autobiography, Wild Swans, it has found dramatic shifts in the characterization of Mao in the Chinese translation by Pu Zhang, published in Taiwan, which alters the overall narrative. This paper proposes a categorization of equivalences and shifts of linguistic agency based on a text-based analysis, thus contributing to a more systematic categorisation of the translation of agency.